A systematic review and meta-analysis of fall incidence and risk factors in elderly patients after total joint arthroplasty. Issue 50 (11th December 2020) - Liu, Yang; Yang, Yanjiang; Liu, Hao; Wu, Wenyuan; Wu, Xintao; Wang, Tao
Abstract: Background: Falls in the elderly have become a serious social problem worldwide. Approximately a third of persons fall at least once in the year after total joint arthroplasty (TJA), but preventing and treating falls is still challenging in clinical practice. Until now, no formal systematic review or meta-analysis was performed to summarize the risk factors of falls after TJA. The present study aimed to quantitatively and comprehensively conclude the risk factors of falls after TJA in elderly patients. Methods: The electronic databases to be searched include CNKI, Embase, Medline, and Cochrane central database (all up to November 2018). All studies on the risk factors of falls after TJA in elderly patients without language restriction were reviewed. Process of evaluation of identified studies and extraction of data were independently conducted by 2 reviewers, qualities of included studies were assessed using the Newcastle–Ottawa Scale. Data were pooled and a meta-analysis completed. All analyses were performed by the software Stata 11.0. Results: A total of 14 studies were included, which altogether included 1284456 patients with TJA, of them 12879 cases of falls occurred after surgery, suggesting the accumulated incidence of 13.1% and the prevalence of in-hospital falls was 1.0%. This study has provided evidence for the preventing of falls in the elderly patients who were underwent TJA. Outcome measures include advanced age, female, Overweight (BMI≥25 kg/m 2 ), falls history, use of walking aid, diabetes, cardiac disease, hypertension, COPD and depressive symptoms. The ABC Scale was significantly negatively correlated with falls after lower extremity joint replacement. Conclusions: Related prophylaxis strategies should be implemented in elderly patients involved with above-mentioned risk factors to prevent falls after TJA.